Molecular genetic analysis of Rubinstein–Taybi syndrome in Russian patients - Ismagilova, Olga R.; Adyan, Tagui A.; Beskorovainaya, Tatiana S.; Polyakov, Alexander V. (Frontiers in Genetics, 2025)
IntroductionRubinstein–Taybi syndrome (RSTS) is one of the many forms of syndromic intellectual disability, occurring in the population with a frequency of 1: 100–125 thousand newborns. The specific phenotype of patients enables the so-called “portrait” diagnosis of classical cases of RSTS, followed by the analysis of the CREBBP and EP300 genes, whose association with RSTS has been confirmed. Nevertheless, for approximately half of the patients in various cohorts, the diagnosis cannot be confirmed.MethodsIn this paper we present the results of a study of 158 Russian patients referred for molecular diagnosis of RSTS using multiplex ligation-dependent probe amplification (MLPA) and next-generation sequencing (NGS).ResultsPathogenic and likely pathogenic variants were identified in 67 patients (42.4%), of which 62 (39%) were in CREBBP and 4 cases (2%)—in EP300. In one case, a known pathogenic variant in SRCAP, associated with Floating–Harbor syndrome (FHS), which is phenotypically similar to RSTS, was also identified; therefore, the possibilities and prospects for differential diagnosis were considered.